Model of the Opportunity Recognition Process - Stefan TRZCIELINSKI (Communications of International Proceedings, 2021)
Numerous studies show that enterprises which are able to recognize and take advantage of opportunities benefit financially and are more competitive. Researchers dealing with recognition of opportunities focus mainly on the notion of entrepreneurial alertness and factors on which it is dependent, leaving behind how this process works, and the fact that its course in discovering opportunities is significantly different than in creating them. Based on case studies in this article, we attempt to fill this gap by presenting a model of the process of recognizing and taking advantage of opportunities.
Keywords: Opportunity Recognition; Opportunity Creation; Opportunity Discovery; Agility